The Influence of PAD, DAU, and DBH on the Allocation of Capital Expenditure in City Districts in the Province of Bali in 2018-2021 - Ananta, Basitho Majid Endi; Erawati, Ni Made Adi (Transpublika Publisher, 2025)
This study aims to analyze the influence of PAD, DAU, and DBH on the allocation of capital expenditure in Bali Province between 2018 and 2021. Bali Province as one of the main tourism centers in Indonesia faces challenges in managing its regional financial resources, especially local revenue (PAD), General Allocation Funds (DAU), and Profit-Sharing Funds (DBH). This research is ex post facto research. The scope of this research is Bali Province which includes 1 city and 8 districts. The data used in this research was obtained from observations made on the 2018-2021 APBD realization report. Multiple linear regression was used in the analysis to explore how different factors are related to changes in the allocation of capital expenditure. The results indicated that local revenue has a favorable effect on the allocation of capital expenditures. Similarly, the allocation of general funds was shown to positively influence changes in capital expenditure allocation. On the other hand, profit sharing funds did not show any notable impact on changes in capital expenditure allocation. These research outcomes could serve as a foundation for improving the allocation of capital expenditure within the Bali Provincial Government. This can be done in several ways, namely by increasing local original income and paying attention to general allocation funds.